ANALISIS HAK DAN KEWAJIBAN PARA PIHAK PADA PERJANJIAN JUAL BELI PIUTANG DALAM PEMBIAYAAN ANJAK PIUTANG - MUHAMMAD HENDRA (USU LAW JOURNAL, 2013)
The right and obligation that become a heap in the bond of contract will be a holy symbol to all the parties, together keep it in order to what become the basic interest  of all the parties could be protected and realized finely in the same manner as must. On Pacta Sun Servanda principle that is the person who pledge to do something must fulfill his or her promise along with Partie Autonomie or Freedom Of Contract that absolve everyone to make an agreement of contract and then the contract will be the law to all the party who made it, as long as not to be in contradiction wih all the rules and regulations that obtain an all the other proper norms. Until for the next future couldn’t happen what says as WanPrestasi (reluctant of promise) by one party that finally could have negative impact to all the process of trade transactions that ongoing.In particular in factoring trade transactions that day after day getting wriggle especially after legalized and precepted in Keppres No.61 of 1988 on date December 20 of 1988 about Financing Institution or be acquainted with policy package of December 1988 that distincted with releasing judgement letter of The Minister Of Finance No. 1251/KMK.013/1988 about Finance Company that revised with Regulation Of The Minister Of Finance No.84/PMK.012/2006 about Finance Company. Keywords: Factoring, The right and obligation of the parties in factoring agreement,Wan Prestasi (reluctant of promise) and the settlement dispute of  the parties in factoring.